Human capital, trade openness and CO₂ emissions: Evidence from heterogeneous income groups - Muhammad Ali Iqbal; Muhammad Tariq Majeed; Tania Luni (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2021)
This study examines the impact of trade openness, urbanization, and human capital on environmental degradation using the panel data of 126 economies for the years 1971-2020. The study also extends the analysis for four sub-panels namely, high-income economies (HIC), upper-middle-income economies (UMIC), lower-middle-income economies (LMIC), and low-income economies (LIC) by using fully modified least squares (FMOLS), dynamic ordinary least squares (DOLS), fixed effects (FEM), random effects (REM), and system GMM. This study uses the environmental impact of the population, affluence, and technology (IPAT) model. The main result of the study reveals that openness to trade has a harmful impact on the environment in the global, upper-middle-and low-income economies, although it shows a benign effect on the environment in high-income economies. Moreover, trade has an insignificant influence on the environment in lower-middle-income countries, but a negative significant impact in high-income economies. Urbanization degrades the environment in all economies except in low-income economies where it improves environmental quality. Meanwhile, results alsoshow that enhancement in human capital will lessen emissionsin all economies. Human capital has the potential to curb the level of emissionsin almost all income economies. Therefore, economies should invest in human capital to combat emissions.
Keywords: 330; carbon dioxide emissions(CO2); environmental quality; human capital; IPAT; trade openness; urbanization